2013
DOI: 10.1111/jvim.12059
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐articular Histiocytic Sarcoma and Previous Joint Disease in Bernese Mountain Dogs

Abstract: Background: Peri-articular histiocytic sarcoma (PAHS) occurs in dogs, including Bernese Mountain Dogs (BMD). An etiologic relationship with previous joint disease has not been documented.Hypothesis: Peri-articular histiocytic sarcoma in BMD will be more frequently encountered around previously diseased joints compared with normal joints.Animals: 920 European BMD. Methods: A retrospective study, in which data were obtained through an Internet questionnaire and from 2 veterinary pathology laboratories. Archived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
3
24
1
Order By: Relevance
“…Both exposure variables reported here, diagnosis with an orthopedic condition and treatment with anti‐inflammatory medications, could be considered surrogate indicators for inflammation, but direct measurement of inflammatory processes would not have been possible given the study design and retrospective nature of data collection. However, the findings of our study are consistent with associations that have been reported between inflammatory disorders and cancer in both humans and dogs, and thus support the hypothesis that chronic inflammation is associated with the occurrence of HS in BMD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both exposure variables reported here, diagnosis with an orthopedic condition and treatment with anti‐inflammatory medications, could be considered surrogate indicators for inflammation, but direct measurement of inflammatory processes would not have been possible given the study design and retrospective nature of data collection. However, the findings of our study are consistent with associations that have been reported between inflammatory disorders and cancer in both humans and dogs, and thus support the hypothesis that chronic inflammation is associated with the occurrence of HS in BMD.…”
Section: Discussionsupporting
confidence: 92%
“…Both modeling approaches identified similar relationships with the outcome of HS in BMD, which strengthens conclusions that might be drawn from our study. The relationship between orthopedic conditions and HS has been examined previously and it was reported that BMD were >5 times more likely to develop peri‐articular HS in a previously diseased joint than a dog with no prior diagnosis of joint disease . To the authors’ knowledge, however, associations between treatment with prescription anti‐inflammatory medications and a decreased risk of developing HS have not been reported previously in either dogs or humans.…”
Section: Discussionmentioning
confidence: 93%
“…In the absence of a defined intracranial subdural space, both primary and disseminated HS involve both the meninges and the brain parenchyma, and most other intracranial neoplasia is not associated with marked CSF pleocytosis, also supporting an argument for inherent differences in the pro‐inflammatory nature of the primary versus disseminated HS subtypes. Articular or periarticular HS also has been associated with a marked inflammatory response, and associations have been made between prior injury and inflammation involving the joint and the development of HS . No direct evidence supports underlying inflammation as a predisposing factor for the development of HS, but the link between inflammation and a variety of cancers is well documented .…”
Section: Discussionmentioning
confidence: 99%
“…18 A history of anterior cruciate rupture or other traumatic injury to joints is associated with the development of articular HS. 18,82 Synovitis has been reported in association with rupture of the cranial cruciate ligament. T cells and dendritic cells are major components of the inflammatory response.…”
Section: Distinctive Histiocytic Sarcoma Syndromesmentioning
confidence: 99%